The Effect of School Leadership, Academic Supervision, and Work Motivation on Teacher Performance - Mustahyi Mustahyi; Joni Joni Rohkmat; Fahruddin Fahruddin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2021)
This study aims to examine the effect of principal leadership, academic supervision, and work motivation on teacher performance. The method used is a survey method with a quantitative correlational approach. The research sample consisted of 136 teachers (86 male teachers and 50 female teachers) from 4 State Senior High Schools in East Lombok Regency, namely SMA Negeri 1 Aikmel, SMA Negeri 1 Wanasaba, SMA Negeri 1 Pringgabaya, and SMA Negeri 1 Suela. The research instrument in the form of a questionnaire was given to respondents directly after testing the validity and reliability. The data analysis technique used a simple regression test and multiple regression tests followed by a correlation test. Data analysis results based on the coefficient of determination for each research variable on teacher performance obtained the coefficient of determination of work motivation of 47.8%, academic supervision of 45.5%, and the variable of principal leadership of 44.4%. While the results of the coefficient of determination collectively were 53.8%. Thus, it can be concluded that both individually and collectively, the principal's leadership, academic supervision, and work motivation affect teacher performance.